Some thoughts on the concepts of ‘truth’ and ‘proof’ in relation to the possibility of proving future events (Perspectivas de las Ciencias Económicas y Jurídicas, 2025)
The concepts of “truth” and “evidence”, intrinsically ambiguous and vague, are constantly used in the framework of procedural discussions related to the demonstration of facts. In this context, judicial operators often refer to one or the other in an indistinct or confusing manner, without drawing distinctions as to whether they are facts of the past or facts of the future. This work proposes to show the main distinctions that exist in relation to both concepts, in each of these areas, and their potential impact. To do this, we will focus, particularly, on the analysis of procedural risk in the framework of the issuance of precautionary measures depriving us of liberty.
Keywords: truth; proof; future facts; procedural risk